O żeńskich formach nazw zawodów, tytułów i stanowisk w języku polskim - Wtorkowska, Maria (Slavistična revija, 2019)
The subject of this article is feminatywy (feminine forms of professions, titles, and posts) in Polish, as well as the relationship between gender and the grammatical category of personal nouns. The article presents ways of deriving feminine forms, their formal exponents, and discusses recent changes in the creation and use of feminine forms, including reasons for impediments to feminine derivation and the emphasis on gender fluctuation.
Keywords: besedotvorje; feminine forms; gender (linguistics); grammatical gender; naming of persons; poimenovanje oseb; Polish language; poljščina; slovnični spol; spol (jezikoslovje); word formation; ženske oblike